Reorientação teórica ou ruptura tardia? Um estudo teórico-bibliográfico sobre a hipótese da descontinuidade da Teoria Crítica de Max Horkheimer - Rodrigues, Bruno Pereira (2022)
The foundations of Max Horkheimer's critical theory flourish in his youthful aphorisms written between 1926-1931 and mainly in the articles published in Zeitschrift für Sozialforschung (Journal for Social Research). Nevertheless, his later formulations, developed especially in Dialectics of Enlightenment and The Eclipse of Reason, occupy a fundamental place in the body of his work, as well as in the history of twentieth century philosophy. The present dissertation aims at outlining possible continuities or future ruptures in critical theory after 1940, when Horkheimer established a closer intellectual relationship with Theodor W. Adorno. The fundamental problem that seeks to be clarified in the subsequent pages is whether there would really be an unequivocal continuity in Horkheimer's work. Could one assume that what prevailed in his philosophy was theoretical reorientation or rupture? This dissertation argues that there is a theoretical reorientation from 1930 to 1940, however, this reorientation rises to the condition of rupture in the following decades, in his notes and late notes. The research hypothesis is that there would be a late rupture in Horkheimer's philosophy when considering the passage from Interdisciplinary Materialism to the critique of Reason and, belatedly, to negative theology and the longing for the Whole Other.